Di‐lysine motif‐like sequences formed by deleting the C‐terminal domain of aquaporin‐4 prevent its trafficking to the plasma membrane. (26th February 2021) - Chau, Simon; Fujii, Atsushi; Wang, Yingqi; Vandebroek, Arno; Goda, Wakami; Yasui, Masato; Abe, Yoichiro
Abstract: Aquaporin‐4 is a transmembrane water channel protein, the C‐terminal domain of which is facing the cytosol. In the process of investigating the role of the C‐terminal domain of aquaporin‐4 with regard to intracellular trafficking, we observed that a derivative of aquaporin‐4, in which the C‐terminal 53 amino acids had been removed (Δ271‐323), was localized to intracellular compartments, including the endoplasmic reticulum, but was not expressed on the plasma membranes. This was determined by immunofluorescence staining and labeling of the cells with monoclonal antibody specifically recognizing the extracellular domain of aquaporin‐4, followed by confocal microscopy and flow cytometry. Deletion of additional amino acids in the C‐terminal domain of aquaporin‐4 led to its redistribution to the plasma membrane. This suggests that the effect of the 53‐amino acid deletion on the subcellular localization of aquaporin‐4 could be attributed to the formation of a signal at the C terminus that retained aquaporin‐4 in intracellular compartments, rather than the loss of a signal required for plasma membrane targeting. Substitution of the lysine at position 268 with alanine could rescue the Δ271‐323‐associated retention in the cytosol, suggesting that the C‐terminal sequence of the mutant served as a signal similar to a di‐lysine motif. Abstract : Deletion of the C‐terminal 53 amino acids of AQP4 inhibits cell‐surface expression. Mutant AQP4 localizes to intracellular compartments, including the ER. A sequence at the C terminus, including SKAA, functions as a di‐lysine motif‐like intracellular retention signal